Student’s Effort’s Understanding Word Spelling - Yani Lubis; Mutiara Qalbiyah Marfa; Salwa Aulia Chaniago (Journal of Constitutional, Law and Human Rights, 2025)
In everyday life as humans we cannot be separated from language. This activity can be carried out through spoken language and written language. In children's development, language has an important role both from a social, emotional and intellectual perspective which supports success in understanding the field of study. Language consists of 4 stages, namely speaking, listening, reading and writing (Susanto, 2013 p. 241). Spelling is an important element in communicating in writing, in addition to using correct spelling, it is the basis for using English well and correctly. However, students often experience difficulties in understanding and applying the spelling of words correctly, so efforts need to be made so that students can understand and master the spelling of words properly and correctly